The role of ITO resistivity on current spreading and leakage in InGaN/GaN light emitting diodes. (November 2017) - Sheremet, V.; Genç, M.; Elçi, M.; Sheremet, N.; Aydınlı, A.; Altuntaş, I.; Ding, K.; Avrutin, V.; Özgür, Ü.; Morkoç, H.
Abstract: The effect of a transparent ITO current spreading layer on electrical and light output properties of blue InGaN/GaN light emitting diodes (LEDs) is discussed. When finite conductivity of ITO is taken into account, unlike in previous models, the topology of LED die and contacts are shown to significantly affect current spreading and light output characteristics in top emitting devices. We propose an approach for calculating the current transfer length describing current spreading. We show that an inter-digitated electrode configuration with distance between the contact pad and the edge of p-n junction equal to transfer length in the current spreading ITO layer allows one to increase the optical area of LED chip, as compared to the physical area of the die, light output power, and therefore, the LED efficiency for a given current density. A detailed study of unpassivated LEDs also shows that current transfer lengths longer than the distance between the contact pad and the edge of p-n junction leads to increasing surface leakage that can only be remedied with proper passivation. Highlights: Finite conductivity of ITO current spreading layer in LEDs is taken into account. Transfer length in current spreading layer defines effective area of LED. Power of light and series resistance of LED is proportional to its effective area. Interdigitated LED chip configuration allows LED chip effective area increasing. The passivation of LED edges is required for optimum LED chip configuration.